Heritable IUGR and adult metabolic syndrome are reversible and associated with alterations in the metabolome following dietary supplementation of 1‐carbon intermediates. Issue 6 (10th March 2015) - Seferovic, Maxim D.; Goodspeed, Danielle M.; Chu, Derrick M.; Krannich, Laura A.; Gonzalez‐Rodriguez, Pablo J.; Cox, James E.; Aagaard, Kjersti M.
ABSTRACT: Metabolic syndrome (MetS), following intrauterine growth restriction (IUGR), is epigenetically heritable. Recently, we abrogated the F2 adult phenotype with essential nutrient supplementation (ENS) of intermediates along the 1‐carbon pathway. With the use of the same grandparental uterine artery ligation model, we profiled the F2 serum metabolome at weaning [postnatal day (d)21; n = 76] and adulthood (d160; n = 12) to test if MetS is preceded by alterations in the metabolome. Indicative of developmentally programmed MetS, adult F2, formerly IUGR rats, were obese (621 vs. 461 g; P < 0.0001), dyslipidemic (133 vs. 67 mg/dl; P < 0.001), and glucose intolerant (26 vs. 15 mg/kg/min; P < 0.01). Unbiased gas chromatography‐mass spectrometry (GC‐MS) profiling revealed 34 peaks corresponding to 12 nonredundant metabolites and 9 unknowns to be changing at weaning [false discovery rate (FDR) < 0.05]. Markers of later‐in‐life MetS included citric acid, glucosamine, myoinositol, and proline ( P < 0.03). Hierarchical clustering revealed grouping by IUGR lineage and supplementation at d21 and d160. Weanlings grouped distinctly for ENS and IUGR by partial least‐squares discriminate analysis (PLS‐DA; P < 0.01), whereas paternal andmaternal IUGR (IUGR pat /IUGR mat, respectively) control‐fed rats, destined for MetS, had a distinct metabolome at weaning (randomForest analysis; class error < 0.1) and adulthood (PLS‐DA; P < 0.05). In sum, we have found that alterations in the metabolome accompany heritable IUGR, precede adult‐onset MetS, and are partially amenable to dietary intervention.— Seferovic, M. D., Goodspeed, D. M., Chu, D. M., Krannich, L. A., Gonzalez‐Rodriguez, P. J., Cox, J. E., Aagaard, K. M. Heritable IUGR and adult metabolic syndrome are reversible and associated with alterations in the metabolome following dietary supplementation of one‐carbon intermediates. FASEB J. 29, 2640‐2652 (2015). www.fasebj.org